Implementation of a task-shared psychosocial intervention for perinatal depression in South Africa: A grounded theory process evaluation - Thandi Davies; Crick Lund; Marguerite Schneider (Elsevier, 2022)
Perinatal depression carries significant levels of disability for both women and their infants, but there is a large treatment gap for this condition in low and middle-income countries (LMICs). To address this gap, task-sharing using community health workers (CHWs) to provide psychosocial interventions for perinatal depression is increasingly common. Many of these interventions have shown significant positive effects on maternal mood, however not all have done so. This study used data from a task-shared psychosocial intervention for perinatal depression in Cape Town, South Africa, the 'Africa Focus on Intervention Research for Mental Health' (AFFIRM-SA) randomised controlled trial (RCT). It aimed to examine the processes that occurred within the delivery of the counselling intervention, and to use these findings to provide recommendations for psychosocial task sharing in LMICs.A grounded theory analysis was conducted of 234 counselling session transcripts from 39 randomly selected participants from the RCT. This revealed that the effectiveness of the intervention was compromised by the negative influence of participants' socio-economic context, and by counselling strategies that did not align with what was intended in the counselling manual. Despite this, participants provided spontaneous accounts of improvement in mood and cognition, and reasons for these improvements, interpreted as elements that were therapeutically effective for them. Most of these elements aligned with previously identified 'common elements' of therapy.Recommendations for future research and practice include conducting participatory formative research, using an iterative and responsive research design informed by implementation science, incorporating contextually appropriate strategies in interventions such as addressing social determinants of mental health, conducting intensive training and supervision, adopting a staged approach to managing depression, and using common elements of therapy as the basis for psychosocial interventions.